Penggunaan Persetujuan Medis Sebagai Alat Bukti - Tamher, Gunawan; Saija, Ronald; Labetubun, Muchtar Anshary Hamid (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Informend Consent is an agreement that is given after receiving information. Approval of action to be taken by the doctor must be done without any element of coercion.Purposes of the Research: The purpose of this paper is to determine the use of Informend Consent as evidence in civil disputes and the factors that influence it. Methods of the Research: The research method used is normative juridical, the approach used in this research is the statutory approach, conceptual approach and case approach. Sources of legal materials used are primary legal materials, secondary and tertiary legal materials. The technique of collecting legal materials carried out in this research is through a literature study, then analyzed using qualitative methods.Results of the Research: The use of medical approval as evidence of decision Number 114/Pdt.G/2020/PN Bjm was not carried out thoroughly so that it resulted in material and immaterial losses. Factors that influence the use of medical consent as evidence include; lack of patient knowledge, answering patient doubts, confirming procedures in laws and regulations, proving doctors in the feasibility of doing something related to medical work.